Feminist Criticism of Traditional Understanding of Women's Roles in Islam - Suud Sarim Karimullah; Siti Rutbatul Aliyah (An-Nisa' Journal of Gender Studies, 2023)
This study comprehensively reveals the intellectual and social dynamics of the significant impact of patriarchal norms embedded in tradition on the limited understanding of gender roles in the Islamic context. By integrating the approaches of literature study and analysis comprehensively, this study offers a strong theoretical foundation for understanding the evolution of views on the role of women in Islam. The study's results highlight the important role of feminist criticism in dismantling the social construction of gender roles in Islam. Patriarchal norms that limit the role of women in Muslim society are not an essential part of the teachings of Islam but the result of interpretation by men in power. It also gave rise to debates about ambiguous interpretations of religious texts, opening up opportunities for interpretations in favor of gender equality and women's rights. Moreover, feminist criticism is not a threat but a constructive attempt to revive equality in Islam and promote an inclusive and progressive understanding of the role of women in modern Muslim society.